A novel hybrid radiative and ventilative cooling system integrated with latent heat storage for buildings in hot-arid climates - Zein Elabdein, Rami (2019)
The use of phase change material (PCM) as potential energy storage for cooling of buildings using night low-temperature air is one of the promising sustainable strategies referred to as “the free cooling of buildings”. Application of this strategy in hot climates is not exploited, and most of the published work has been carried out in moderate and continental climates. Moreover, the free cooling potential is insufficient under extreme summer conditions, owing to the small temperature difference between the PCM and the ambient air in addition to the limited available charging time. Therefore, with the aim of sustaining and enhancing the free cooling potential in such disadvantageous conditions, an innovative hybrid nocturnal radiative and ventilative cooling system using latent heat storage (NRV-LHS) has been proposed in this study. Such a combined system has not been adduced in previous studies.